Ipilimumab in real-world clinical practice: efficacy and safety data from a multicenter observational study. (4th July 2017) - Russi, Alberto; Damuzzo, Vera; Chiumente, Marco; Pigozzo, Jacopo; Cesca, Marco; Chiarion-Sileni, Vanna; Palozzo, Angelo Claudio
Abstract : In patients with metastatic melanoma, ipilimumab has been shown to improve long-term survival. This observational multicenter study reports clinical outcomes of 418 patients treated with second-line ipilimumab from February 2013 to August 2014. Median overall survival (OS) was 6.43 months (95%CI: 5.45–7.42; n  = 300), while median progression-free survival (PFS) was 3.7 months (95%CI: 3.23–4.17; n  = 188). Demographic factors, such as sex or number of previous therapies did not affect OS. Survival was shorter in patients with ECOG > 0 (Eastern Cooperative Oncology Group, Performance Status) ( p  < 0.001), while a longer OS was found in patients who completed all four therapy cycles ( p  < 0.001). Adverse events of any grade were reported for 66% of patients (mainly cutaneous and gastrointestinal), but most were low grade and easily managed. Adverse events of grades 3–4 were observed in 13% of patients. This study confirmed the efficacy and safety of this treatment in real practice.